(untitled) (Global Journal of Human-Social Science, 2018)
One of the main political issues in Indian politics is connected to language problem. After India’s independence the government decided that the official language of India will be Hindi. In this paper, I have attempted to take a look at study of politics of languages in late colonial India. A set of languages used by political operators in the Indian scenario where the diverse political scenarios play a vital role in the linguistic matters viz, organization of languages, language policies and planning, minority and majority languages. The motive of this paper is to present the historical overview of language politics in India and its impact on the documentation and organization of languages. How the political concern influences the up gradation and degradation of the status of a language. It further illustrates how the government policies used for the development of majority languages, causing a threat to minority languages.